2020
DOI: 10.3390/nano10030587
|View full text |Cite
|
Sign up to set email alerts
|

Ecofriendly Synthesis and Insecticidal Application of Copper Nanoparticles against the Storage Pest Tribolium castaneum

Abstract: In spite of great developments in the agricultural field and plant productivity in the last decades, the concern about the control of agricultural pests is still continuous. However, pest management is expected to have more effects from nanomaterials by providing innovative solutions. The current study confirms the biotransformation of copper nanoparticles (CuNPs) using a cell-free culture extract of metal copper-resistant bacteria Pseudomonas fluorescens MAL2, which was isolated from heavy metal-contaminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(57 citation statements)
references
References 54 publications
4
53
0
Order By: Relevance
“…2). The present ndings are in agreement with the recent ndings [30]. The aforementioned studies reported that the appearance of green color color is due to reduction of copper sulfate and its bioconversion to CuNPs.…”
Section: Results and Discusionsupporting
confidence: 94%
See 1 more Smart Citation
“…2). The present ndings are in agreement with the recent ndings [30]. The aforementioned studies reported that the appearance of green color color is due to reduction of copper sulfate and its bioconversion to CuNPs.…”
Section: Results and Discusionsupporting
confidence: 94%
“…Although Sudhir et al [32] demonstrated that the biogenic CuNPs were characterized by UV-Vis spectrophotometer showing a typical resonance (SPR) at about 631 nm which is speci c for CuNPs. CuNPs were studied recently by [30] at 200-1000 nm wavelength range and it has absorbance at 550 to 650 nm.…”
Section: Results and Discusionmentioning
confidence: 99%
“…Curcumin nanoparticles in this study were synthesized from Bacillus subtilis LA4, which was isolated from soil samples that were collected from different sites next to the plant rhizosphere in Sharqia Governorate, Egypt [17][18][19]. Under the optimum conditions of temperature, pH, incubation time, and other parameters, curcumin nanoparticles were produced.…”
Section: Source Of Curcumin Nanoparticlesmentioning
confidence: 99%
“…According to the proposed mechanism of CuNP stabilization with capping agents [ 15 , 16 , 54 , 55 , 56 , 57 , 58 ], the ionic groups in the alkyl side chains of CPE would be mainly responsible for CuNP stabilization; however, the high electron density on the surface of the π-conjugated polyelectrolyte could also play a role in the CuNP stabilization. To test this hypothesis, theoretical calculations were performed, and the results are detailed in Section 3.2 .…”
Section: Resultsmentioning
confidence: 99%